Análise dos polimorfismos, A637G do gene TAP1, A121C do gene ENPP1, C677T e A1298C do gene MTHFR e isoformas E2, E3 e E4 do gene APOE e de fatores de risco para doença cardiovascular em mulheres portadoras de Síndrome de Turner - Oliveira, Kelly Cristina de [UNIFESP] (2010)
Background: Epidemiological studies showed a reduction of up to 13 years in life expectancy of Turner Syndrome (TS) patients compared to normal women, being the main cause of cardiovascular disease (CVD) mortality. Hypertension (SAH) diabetes mellitus (DM) and dislipidemy are important risk factors for CVD that are highly prevalent in this syndrome. TAP1, ENPP1 and APOE genes are associated with cardiovascular risk for being involved in the pathogenesis of hypertension, DM and hypercholesterolemia, respectively. The aim of this study was to analyze the frequency of polymorphism of these genes in TS patients. Methods: Seventy eight TS patients and 372 healthy individuals with no personal and familial history of CVD were assessed for polymorphisms of genes TAP1 and ENPP1 by Restriction fragment length polymorphism (RFLP). Isoforms of APOE gene were genotyped by qPCR. Results: Analysis of AA, GG and AG genotypes frequencies of A637G TAP1 polymorphism in TS patients were, respectively, 7.7%, 52.6% and 39.7%, while the control group presented 11.0%, 55.0% and 34.0% (p=0.4584). The frequency of genotypes for ENPP1 A121C polymorphism in the ST patients were: AA 42,3,0%, AC 48.7% and CC 9.0% and 45.0%, 42.0% and 12.0% in controls (p=0.5169). The frequency of genotypes of APOE gene in TS patients and controls were, respectively: E3E3 68.3% and 61.5%, E2E3 6.3% and 12,4%, E3E4 24.1% and 22,6%, E2E2 0% and 1.0%, E4E4 0% and 1.3% and E2E4 1.3% and 1.1%, (p=0,864). Conclusion: There were no correlations between the frequencies of TAP1, ENPP1 and APOE polymorphisms and CVD risk in women with TS.